Use of complementary and alternative medicine (CAM) methods by cancer patients admitted to oncology polyclinic and evaluation of these methods for life quality (Annals of Medical Research, 2021)
None
Keywords: Cancer; Phytotherapy; Complementary Therapies; Alternative Medicine.